2011
DOI: 10.1021/es201459c
|View full text |Cite
|
Sign up to set email alerts
|

Greenhouse Gas Emissions from the Consumption of Electric and Electronic Equipment by Norwegian Households

Abstract: The number of electric and electronic equipment (EEE) owned by households has multiplied in the recent decade. We investigate the climate implications of the purchase, use and disposal of EEE by Norwegian households in 2008. While traditionally, large electric appliances such as washing machines, dryers, refrigerators and freezers have been responsible for most of the electricity use in households apart from heating and hot water, our results indicate that computers, TV sets and other electronic equipment are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 37 publications
0
27
0
Order By: Relevance
“…This is because energy consumption is a source of several environmental problems, as Suri and Chapman [10] underlined. Kounetas [37] found that energy consumption accounts for approximately 80% of anthropogenic GHG emissions in the EU, while several studies around the world also corroborated that household electricity use is directly responsible for significant GHG emissions (e.g., [38,39]). …”
Section: Contextual Background With a Literature Reviewmentioning
confidence: 97%
“…This is because energy consumption is a source of several environmental problems, as Suri and Chapman [10] underlined. Kounetas [37] found that energy consumption accounts for approximately 80% of anthropogenic GHG emissions in the EU, while several studies around the world also corroborated that household electricity use is directly responsible for significant GHG emissions (e.g., [38,39]). …”
Section: Contextual Background With a Literature Reviewmentioning
confidence: 97%
“…Hertwich and Roux's (2011) investigation of the climate implications of the use of household electric and electronic equipment (EEE), for example, shows TV sets and other EEE to have significant lifecycle GHG emissions. Panzone et al (2013), on the other hand, have designed an index to measure the environmental sustainability of household food consumption based on consumer preferences and scanner data provided by a UK food retailer.…”
Section: Background Of Hce Researchmentioning
confidence: 99%
“…The environmental profile of a wide range of products is affected by one or several of these behavioral factors, for example, in terms of energy and resource use, emission release and waste production (Peattie 2010). Several life cycle assessment (LCA) studies present a contribution of the use phase at the level of 50-80 % of the overall life cycle impacts (e.g., household electric device, Hertwich and Roux 2011). This means that variation in use phase may greatly impact the overall results and the uncertainties thereof.…”
Section: Introductionmentioning
confidence: 99%